Penguatan Ekonomi Berbasis Pemberdayaan Masyarakat Melalui Inovasi Pasar Keramat Di Desa Warugunung - Nur Aini, Elsa; Muhaimin, Hikmah; Yudha Utama, Jenny (MAJAPAHIT POLICY, 2024)
This study aims to determine how economic strengthening based on community empowerment through innovation of sacred market in Warugunung village, Pacet District, Mojokerto Regency and the causes of obstacles/conflicts that occur. This study uses a descriptive method with a qualitative approach. Data were analyzed through interview techniques, direct observation in the field, and documentation. The results of this study reveal that the Pasar Keramat administrators, with assistance from the Yayasan Bambu Lingkungan Lestari (YBLL), PT. Multi Bintang Indonesia, and the Warugunung Village Government, Pacet District, Mojokerto Regency, have made various efforts to empower the community in Warugunung Village, Pacet District, Mojokerto Regency. These efforts are realized through innovation by building the Pasar Keramat, accommodation facilities, and UMKM galleries. In addition, community empowerment is carried out through various trainings, such as bamboo schools, weaving schools, dance schools, visits to the Papringan Market in Central Java, and training in cooking and serving healthy food in Dlanggu Village. These initiatives are expected to provide a significant contribution to strengthening the economy of the Warugunung Village community, Pacet District, Mojokerto Regency